2007
DOI: 10.1111/j.1469-8986.2007.00592.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating dimensional organization in scripts using the pupillary response

Abstract: Scripts are mental representations of activities in memory and are thought to be organized dimensionally in a temporal dimension. We investigated the cognitive strategies during the processing of temporal order of an event sequence to gain insight into the organization of scripts. Subjects were presented with triplets of script events (A - B - C). Fifty percent of the items included sequence violations at different positions within the triplet (late: A - C - B, or early: C - A - B). Reaction times indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…The correlation between behavioral and pupil dilation data revealed only a significant association between RT and LD for the moderate difficulty condition. Some other pupillometry studies have demonstrated no correlations between ER and pupil dilation; however, most studies have reported a correlation between RTs and LD (e.g., Beatty & Lucero-Wagoner, 2000;Raisig, Welke, Hagendorf, & van der Meer, 2007;Nuthmann & van der Meer, 2005). The partial lack for a missing correlation between RT and LD might be due the procedure on how the maximum pupil dilation was determined in this study.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The correlation between behavioral and pupil dilation data revealed only a significant association between RT and LD for the moderate difficulty condition. Some other pupillometry studies have demonstrated no correlations between ER and pupil dilation; however, most studies have reported a correlation between RTs and LD (e.g., Beatty & Lucero-Wagoner, 2000;Raisig, Welke, Hagendorf, & van der Meer, 2007;Nuthmann & van der Meer, 2005). The partial lack for a missing correlation between RT and LD might be due the procedure on how the maximum pupil dilation was determined in this study.…”
Section: Discussionmentioning
confidence: 61%
“…Specifically, higher activations in the bilateral IPS corresponded to longer LDs in each of the difficulty conditions. Although the LD is a function of PD since the muscles controlling pupil dilation take time to constrict and relax due to information processing (so it takes longer to dilate more) (Loewenfeld, 1993), the PD and LD do not correlate in most of the studies (e.g., Beatty & Lucero-Wagoner, 2000;Raisig, Welke, Hagendorf, & van der Meer, 2007;Steinhauer & Hakerem, 1992). A specification of the LD to cortical activity may be due to the finer time scale of the pupillometry compared to fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase is significantly greater when task demands are high compared to when task demands are low. This is the case when a stimulus is unexpected (Gilzenrat Sit down at Brown et al 1999;Siegle et al 2008) or-as we have shown before-when events violate the temporal order (Raisig et al 2007(Raisig et al , 2010. In this task, when a temporal violation is anticipated, we expect that it is not accompanied by the typical pupillary response that marks increased cognitive effort and resource consumption.…”
Section: Introductionmentioning
confidence: 86%
“…We addressed this question with the triplet-paradigm that we have used in several other studies (Raisig et al 2007(Raisig et al , 2010. In that paradigm, an activity (e.g., going to a restaurant) is presented to activate the component events in long-term memory and produce predictions about the order the events will unfold in.…”
Section: Introductionmentioning
confidence: 99%
“…The size of the pupil is not only affected by light conditions, but also by cognitive and physical efforts and emotional arousal (Beatty and Kahneman 1966;Granholm and Steinhauer 2004;Hess and Polt 1964;Kahneman and Beatty 1967;Loewenfeld 1993). It has been demonstrated throughout various cognitive domains and across different modalities of stimulus presentation that pupil dilation is greater the more difficult the task is (Hess and Polt 1964;Nuthmann and van der Meer 2005;Raisig, Welke, Hagendorf and van der Meer 2007;Verney, Granholm and Marshall 2004). For instance, Hess and Polt (1964) found that pupillary dilation is higher while solving difficult arithmetical problems, such as 11 9 6, than while solving easy problems, such as 4 9 7.…”
Section: Pupillometry As a Way To Assess Resource Allocationmentioning
confidence: 99%